Hemoglobin mRNA Changes in the Frontal Cortex of Patients with Neurodegenerative Diseases - Vanni, Silvia; Zattoni, Marco; Moda, Fabio; Giaccone, Giorgio; Tagliavini, Fabrizio; Haïk, Stéphane; Deslys, Jean-Philippe; Zanusso, Gianluigi; Ironside, James W.; Carmona, Margarita; Ferrer, Isidre; Kovacs, Gabor G.; et al. (Frontiers in Neuroscience, 2018)
Background: Hemoglobin is the major protein found in erythrocytes, where it acts as an oxygen carrier molecule. In recent years, its expression has also been reported also in neurons and glial cells, although its role in brain tissue remains still unknown. Altered hemoglobin expression has been associated with various neurodegenerative disorders. Here we investigated hemoglobin mRNA levels in brains of patients affected by variant, iatrogenic and sporadic forms of Creutzfeldt-Jakob disease (vCJD, iCJD, sCJD, respectively) and in different genetic forms of prion diseases (gPrD) in comparison to Alzheimer’s disease (AD) subjects and age-matched controls. Methods: Total RNA was obtained from the frontal cortex of vCJD (n=20), iCJD (n=11), sCJD (n=23), gPrD (n= 30) and AD (n=14) patients and age-matched controls (n=30). RT-qPCR was performed for hemoglobin transcripts HBB and HBA1/2 using four reference genes for normalization. In addition, expression analysis of the specific erythrocyte marker ALAS2 was performed in order to account for blood contamination of the tissue samples. Hba1/2 and Hbb protein expression was then investigated with immunofluorescence and confocal microscope analysis. Results: We observed a significant up-regulation of HBA1/2 in vCJD brains together with a significant down-regulation of HBB in iCJD. In addition, while in sporadic and genetic forms of prion disease hemoglobin transcripts did not shown any alterations, both chains display a strong down-regulation in AD brains. These results were confirmed also at a protein level. Conclusions: These data indicate distinct hemoglobin transcriptional responses depending on the specific alterations occurring in different neurodegenerative diseases. In particular, the initial site of misfolding event (central nervous system vs peripheral tissue) - together with specific molecular and conformational features of the pathological agent of the disease- seem to dictate the peculiar hemoglobin dysregulation found in prion and non-prion neurodegenerative disorders. In addition, these results suggest that gene expression of HBB and HBA1/2 in brain tissue is differentially affected by distinct prion and prion-like aggregating protein strains. Validation of these results in more accessible tissues could prompt the development of novel diagnostic tests for neurodegenerative disorders.